Esthetic rehabilitation with ceramic laminates: Case report (Research, Society and Development, 2021)
Several factors contribute to alterations in the teeth and consequently in the smile, such as tooth discoloration, caries, aging, chemical erosion and diastemas. With the improvement of the ceramic surface treatment and the adhesion to the substrates, the ceramic laminate veneers guaranteed a definitive space in the dental practice, in view of longevity, functionality and aesthetic final result. It is in this scenario that the present study appears, which purpose is to present in detail a method of closing diastemas with the use of ceramic laminate veneers. A female patient attended at Ceuma University (São Luís-MA), with the main complaint of aesthetic dissatisfaction of her smile. Clinical examination revealed the presence of diastemas which persisted even after orthodontic treatment. The treatment started with tooth whitening followed by the gingivoplasty of one dental element, which presented disharmony in the gingival zenith. Then, the steps of the rehabilitation treatment with ceramic laminates were carried out until cementation. Ceramic laminate veneers represent high quality aesthetic and functional solutions for closing diastemas. Success is directly linked with the correct indication and planning, with sufficiently invasive preparation, knowledge of techniques and materials, thus obtaining an aesthetic and harmonious smile, with great guarantee of longevity.